Prevalence of type 2 diabetes association with rheumatoid arthritis among different obese and non-obese populations of Patna, India - Singh, Amrandra Prasad (International Journal of Research in Medical Sciences, 2019)
Background: Type 2 Diabetes mellitus (T2DM) is the most common non-communicable chronic diseases in developed and developing countries around the world. The study reported the prevalence of diabetes association with rheumatoid arthritis (RA) among different obese and non-obese populations of Patna, India. Methods: This clinic based descriptive study was conducted in Patna city from 1st August 2017 to 30th September 2018. A total 250 patients with diagnosed RA were enrolled. DM was defined according to the ADA recommendations as FBS ≥126mg/dl or oral glucose tolerance test OGTT2 ≥200mg/dl and HbA1c≥6.5. On the basis of the BMI calculated, patients were categorized either as obese or non-obese. Random diabetic detection was done to detect T2DM and followed by proper investigation at clinical laboratories. Patients also asked for hyperglycemic events during initial counselling. Results: Mean BMI in obese was found to be 29.22±3.22 and in non-obese it was 22.99±1.38 (p<0.001). Most of the patients had been type 2 diabetes for more than 5 years duration. In both genders, an increasing trend was observed in the prevalence of type 2 diabetes with increasing BMI. Among these, a total of 198 (79.2%) were found to have diabetes, 115 (58.08%) of these were obese and 83 (41.91%) non-obese (p=0.003). Conclusions: BMI is directly correlated to type 2 diabetes, as T2DM was significantly more common in obese patients with RA compared to non-obese patients with RA. Obese patients with RA had significantly more frequent diabetes.